EDUCATION FOR THE STABLE DEVELOPMENT (ANALYSIS, SCIENTIFIC BASIS, WORLD EXPERIENCE) - G. M. ABDURAHMANOV; G. A. MONAKHOVA; L. Z. MURZAKANOVA; A. G. ABDURAHMANOVA; A. A. BAGOMAEV; Z. A. ALIEVA (Юг России: экология, развитие, 2015)
the analysis of "stable development" notion, the role of education in stable development is revealed in the work, as well as the experience of ecological education in different countries